Modification of Poly(vinyl chloride) by N-Phenyl Itaconimides for the Improvement of Its Thermal Stability - Asma M. Elsharif; Azza A. Al-Ghamdi; Abir S. Abdel-Naby (Journal of Chemistry)
Poly(vinyl chloride) (PVC) is modified by N-phenyl itaconimide derivatives (N-(RPh)IM) as modifying agents or graft comonomers. The resulting modified polymers or graft copolymers were characterized using FTIR and UV/Vis spectrophotometry. The thermal properties of the modified polymers were investigated using thermogravimetry (TGA), which revealed that the synthesized polymers exhibited high thermal stability, as shown from the value of their initial decomposition temperatures and the percentage of weight loss at high temperatures. The polymer modified by 4-bromo itaconimide exhibited the most thermal stability. A mechanism for the modification reaction and the graft copolymerization of PVC was suggested.